The Seasonal and Inter-Annual Fluctuations of Plankton Abundance and Community Structure in a North Atlantic Marine Protected Area - Benedetti, Fabio; Jalabert, Laëtitia; Sourisseau, Marc; Becker, Beatriz; Cailliau, Caroline; Desnos, Corinne; Elineau, Amanda; Irisson, Jean-Olivier; Lombard, Fabien; Picheral, Marc; Stemmann, Lars; Pouline, Patrick (Frontiers in Marine Science, 2019)
Marine Protected Areas have become a major tool for the conservation of marine biodiversity and resources. Yet our understanding of their efficacy is often limited because it is measured for a few biological components, that are generally top predators or commercially interesting species. Documenting the variation of plankton indicators and their covariation with climate is crucial to understand how marine protected areas benefit from ecosystem-based approaches to achieve their conservation targets. Under this perspective, we aim to document the variations in the emerging properties of the plankton to better understand the dynamics of the pelagic fishes, mammals and seabirds that inhabit the region. For the first time, we analyse the temporal variations of the entire plankton community of one of the widest European protected areas, the Parc Naturel Marin de la mer d’Iroise. We make use of several sampling transects carried out in the Iroise Sea from 2011 to 2015 to explore the seasonal and inter-annual variations of phytoplankton and mesozooplankton abundance, composition and size, as well as their covariation with abiotic variables, through multiple multivariate analyses. Both phytoplankton and zooplankton show consistent seasonal patterns in taxonomic composition and size structure but also inter-annual variations. The spring bloom was associated with a higher contribution of large chain-forming diatoms compared to nanoflagellates that dominate in fall and summer. Dinoflagellates show strong inter-annual variations in their relative contribution. The community composition of phytoplankton has a strong impact on the one of mesozooplankton together with the distance to the coast. The size structure of the mesozooplankton community, examined through the ratio of small to large copepods, also displays marked seasonal patterns as larger copepods (members of the Calanidae) are more abundant in spring than in summer and fall. Several hypotheses are proposed to explain the observed temporal patterns and their importance for understanding the dynamics of other components of the food-web (such as sardines) are discussed. This study is a first step towards the inclusion of the planktonic compartment into the planning of the resources and diversity conservation within the Marine Protected Area.